1997
DOI: 10.1002/j.2161-0045.1997.tb00689.x
|View full text |Cite
|
Sign up to set email alerts
|

Vocational Interests: A Look at the Past 70 Years and a Glance at the Future

Abstract: This article reviews the literature on vocational interests. Ten themes about vocational interests are discussed: development, correlates, measurement, homogeneity and differentiation, career choice, sex differences, stability, structure, career counseling, and cultural influences. These 10 themes are similar to major issues discussed by Strong (1943) in his landmark book on interests Vocational Interests of Men and Women. Directions for future research are presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0
4

Year Published

1998
1998
2014
2014

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 101 publications
(106 reference statements)
0
33
0
4
Order By: Relevance
“…Vocational interests are one of the most central constructs in career development (Betsworth & Fouad, 1997). They guide, for example, career choices (Lent, Brown, Nota, & Soresi, 2003) and play a crucial role in vocational and general identity development in adolescence (Vondracek & Skorikov, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Vocational interests are one of the most central constructs in career development (Betsworth & Fouad, 1997). They guide, for example, career choices (Lent, Brown, Nota, & Soresi, 2003) and play a crucial role in vocational and general identity development in adolescence (Vondracek & Skorikov, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Gender predicted interests in numerous cases as expected, with women reporting higher interests in Artistic and Social areas and men reporting higher Realistic and Investigative interests. This pattern of gender differences in interests has been well documented (e.g., Betsworth & Fouad, 1997;Su et al, 2009). Further, gender differences in interests have been noted as one of the more significant sex/gender differences in psychological research (Lubinski, 2000), although the differences between women's and men's interests have narrowed modestly over time (Bubany & Hansen, 2011;Su et al, 2009).…”
Section: Discussionmentioning
confidence: 76%
“…In contrast, a significant difference in favor medium SES was found in mathematics interest. When the literature was reviewed, it was observed that SES is an important variable affecting vocational interest, however within the studies analyzed there was no information about which SES makes difference in which field (Betsworth & Fouad, 1997;Lent, 2005;Patton & McMahon, 2006). Within this study the number of books purchased, the frequency of the participation of parents in social activities, educational and income level of mother and father were used in determining SES.…”
Section: Discussiona and Conclusionmentioning
confidence: 99%
“…Strong (1943) states that interests are permanent and not affected sufficiently by the vocational education and experience for estimating future behaviors. Yet, McArthur (1954) assumes that this relation seems to be changeable by SES (Betsworth & Fouad, 1997).…”
Section: Introductionmentioning
confidence: 99%